MORPHOLOGICAL CHARACTERISTICS OF FLAX AND ITS SIGNIFICANCE - Turlibayeva Z. A.; Tatayeva D. A.; Muminov H. A. (Web of Journals Publishing, 2024)
The article discusses the morphological characteristics of flax and its significance.
Keywords: signs, Linum, genetics, ecology, factor, plant.